Monitoramento biológico para identificação de fonte de poluição em área residencial contígua à instalação do porto de Santos em Guarujá-SP, Brasil - Lima, Liliane Neiva Arruda (2023)
Guarujá, a tourist town in the Baixada Santista – SP, comprises the left bank of the Port of Santos, which is located more precisely in Vicente de Carvalho, a neighborhood with an infrastructure focused on commerce and which has a population of around 150,000 inhabitants. Given the expansion of activities at the trading terminals, the region was surprised with an important logistical bottleneck for the flow of production, which generates intense congestion in the streets close to the port area. The lack of fluidity in traffic culminates in intense emission of gases and particulate matter (PM), resulting in increased pollution. Although the Environmental Company of the State of São Paulo - CETESB is responsible for monitoring air quality, in Guarujá this monitoring is recent and has only one collection station, in an area that is not affected by cargo transport traffic. The monitoring conducts by CETESB is not representative of vehicle emissions, the main source of local pollution. Therefore, this work represents a scientific contribution to the city planning studies of Guarujá, since it provides an assessment of atmospheric pollutant levels associated with vehicular traffic, such as heavy metals, which were determined using an alternative method involving the utilization of bioindicator plants for pollution. Cadmium - Cd, which is a metal commonly found in the composition of diesel, presented concentrations in areas with intense movement of trucks that were 155 times higher than those observed in regions without pollution. Chronic exposure to Cd can cause serious health problems, including but not limited to vomiting, diarrhea, kidney pain, abdominal discomfort, and bone issues. The pollution diagnosis carried out in Guarujá has contributed to the understanding of the complexity of urban environmental problems, providing to the Environment Secretariat - SEMAM inputs for the formulation of public policies aimed at achieving and maintaining the quality of life, as well as promoting fair and balanced socio-environmental conditions.